Ornaments of Flora and Fauna on Traditional Acehnese House - Sofyan Sofyan (Universitas Syiah Kuala, 2014)
This study was aimed to explore ornaments on the Traditional Acehnese House (TAH) in Banda Aceh. Data were obtained by direct survey and interview methods to TAH and owners, carpenters, and community leaders. Secondary data were obtained from literatures, manuscripts, and museums. Ornaments on the TAH are dominated by elements from flora more than fauna. Other ornaments are dominated by clouds, stars, mountains, curved lines, straight lines and geometry. Few numbers of ornaments from fauna were also influenced by the Islam regulation.